Evaluation of Intersection Capacity under One-Way Traffic Management during Eid Al-Fitr at Sicincin, West Sumatra - Feri, Fadel Muhammad; Yossyafra, Yossyafra; Yosritzal, Yosritzal (Jurnal Teknik Sipil, 2026)
West Sumatra Province is one of the main destinations for Eid homecoming traffic in Indonesia, leading to a substantial increase in traffic volume, particularly along the Sicincin–Padang Luar corridor. To reduce congestion, a one-way traffic system was implemented during the H−3 to H+3 Eid period in 2023 and extended to H−3 to H+5 in 2024. However, the effectiveness of this strategy at the Sicincin Intersection requires further evaluation. This study evaluates the operational performance of the Sicincin Intersection during the implementation of the one-way traffic system and proposes suitable intersection control measures. The methodology comprises classified traffic-volume surveys, observations of queue length and delay, intersection performance analysis based on the Indonesian Highway Capacity Guidelines (PKJI), and microscopic simulation using VISSIM. The results show that during the Eid period, the maximum queue length reached approximately 70 m and the average delay per vehicle was 20.65 s in 2023, increasing to approximately 74 m and 21.85 s in 2024. The findings indicate that signalised control outperforms priority control by reducing traffic conflicts and vehicle delays under saturated traffic conditions. However, queue lengths remain influenced by high traffic demand and limited storage capacity.